A Geographic-Layered Data Middleware for Smart Cities - Souza, Arthur; Pereira, Jorge; Batista, Thais; Cavalcante, Everton; Cacho, Nélio; Lopes, Frederico; Almeida, André (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2018)
The smart city concept envisions the use of a plethora of systems providing different data and services to assist public agents in making strategic decisions for the city based on reliable information. However, the high heterogeneity and lack of standardization of these systems and their data challenge the development of value-added applications, which can be enriched with geographic information to allow for more effective actions over the real-world urban space. This paper introduces Smart Geo Layers (SGeoL), a geographic-layered data middleware platform conceived to integrate data provided by heterogeneous sources in a smart city environment. Besides easing such an integration, SGeoL allows correlating data with geographic information and it provides functionalities such as data aggregation, visualization, query, and analysis. This paper also presents the use of SGeoL in the development of a urban planning application as well as results of some computational experiments aimed to assess the performance of the platform.